Fractional order COVID-19 model with transmission rout infected through environment - Yao, Shao-Wen; Farman, Muhammad; Amin, Maryam; İnç, Mustafa; Akgul, Ali; Ahmad, Aqeel (Amer Inst Mathematical Sciences-Aims, 2022)
In this paper, we study a fractional order COVID-19 model using different techniques and analysis. The sumudu transform is applied with the environment as a route of infection in society to the proposed fractional-order model. It plays a significant part in issues of medical and engineering as well as its analysis in community. Initially, we present the model formation and its sensitivity analysis. Further, the uniqueness and stability analysis has been made for COVID-19 also used the iterative scheme with fixed point theorem. After using the Adams-Moulton rule to support our results, we examine some results using the fractal fractional operator. Demonstrate the numerical simulations to prove the efficiency of the given techniques. We illustrate the visual depiction of sensitive parameters that reveal the decrease and triumph over the virus within the network. We can reduce the virus by the appropriate recognition of the individuals in community of Saudi Arabia.
Keywords: COVID-19 model; transmission rout; uniqueness; stability; sumudu transform; Adams-Moulton rule; fractal fractional